The Pankisi Valley and Its Values in Reportage All Lara’s Wars by Wojciech Jagielski - Akram, Sara (Vilnius University Open Series, 2020)
The aim of the article is to analyse values connected with a particular space, presented in the reportage All Lara’s wars by Wojciech Jagielski. Jagielski is one of the most well-known Polish reporters, author of eight reportage books and a large number of news reportages. He worked as a war correspondent for twenty-one years and travelled to many countries in Europe, Asia and Africa. In the introduction part, there has been referred chosen literature on space and values (works of such experts as Janusz Sławiński, Mieczysław Porębski and Jadwiga Puzynina). There are two basic types of space in general human experience – physical and symbolic. Humans have no influence over the first one, but they are able to create their symbolic spaces, using values which are important to them. In European culture value means something perceived as good by a particular subject. Values determine the way of human lives, their decisions and actions. The Pankisi Valley is both a physical and symbolic space. It lies within Georgia, right beside the border with Chechnya (today Russia). Inhabitants of this valley are called Kists and the main character of the book – Lara – is one of them. The Valley is presented as isolated from the rest of the country, because it is surrounded by Caucasus mountains. Thus it is perceived as microcosmos, completely sufficient for people living there, without a need of change. The most important value in Kists’ life is tradition, which meaning has been referred in works of Jerzy Szacki and Kazimierz Dobrowolski. Tradition inherited after ancestors includes such elements as: values, laws, customs and it has determined the rules of coexistence in the valley. Tradition has been accepted by Kists unconditionally, treated almost as something sacred, so it has become a deciding power in their lives. One of its elements is social hierarchy, which puts the elders on the top – everyone else has to respect their decisions. Another important value is stability of reality and events – Kists choose to be subordinated to fate, so they never have to make a single change on their own. Being passive and accepting what comes forward is a way of keeping peace and order in life and guaranteeing security. It also takes off the responsibility of making individual choices as well as their consequences. Thanks to that, every person lives the same life, follows the identical ways in which everything happens. It is worth to emphasize that Kists always perceive such way of life as something positive. Everlasting tradition shapes the constant pace of Kists’ lives and so their axiological space. The Pankisi Valley is perceived mainly as home and community, not only in the meaning of family, but everyone living in the valley. Pankisi is also described as destiny – a place where particular things are destined to happen and cannot be changed.